Seroprevalence of arboviruses in members of United Nations peacekeeping missions in the Central African Republic - Atanasievska Kujović, Sonja; Ristanović, Elizabeta; Djordjevski , Nikoleta; Živić, Maja; Krstić, Milena; Ljubenović, Nenad; Mladenović, Jovan; Trifunović, Sofija; Marjanović, Sonja (Vojnosanitetski pregled, 2025)
Background/Aim. Members of the Serbian Armed Forces participating in the United Nations (UN) Multidimensional Integrated Stabilization Mission in the Central African Republic (CAR) – MINUSCA, are exposed to the bites of the Aedes genus mosquitoes, which are transmitters of some (or certain) arboviruses. The aim of the study was to determine the exposure, risk factors, and prevention and protection measures against infection with arboviruses in members of peacekeeping missions (PKM). Methods. The study included 136 members of UN PKM in CAR in two rotations during 2022/2023, lasting 8 and 6 months. Each respondent had to answer the questions of the designed epidemiological questionnaire for the returnees from PKM. The subjects’ blood sera were tested for specific antibodies against Dengue, Zika, and Chikungunya viruses using an enzyme-linked immunosorbent assay (ELISA) test. Results. The number of seropositive individuals for arboviruses was 48 (35.3%). Most members, 23 (16.9%), were seropositive for the Dengue virus, slightly fewer for the Chikungunya virus, 14 (10.3%), and the fewest were seropositive for the Zika virus, 11 (8.1%). Our research shows that impregnating uniforms with repellent plays a significant role in preventing mosquito bites and the Zika virus infection. The number of days spent in the mission and the factors of gender and age did not show an influence on the occurrence of arbovirus infections. Conclusion. The members of PKM in the CAR have come into contact with Dengue, Zika, and Chikungunya viruses. This indicates that it is necessary to work on the constant improvement of prevention measures and protection of their health, including further serological tests, but also tests for the presence of various infectious microorganisms in this endemic area.
Keywords: arbovirus infections; central african republic; culicidae; hospitals, military; insect repellents; preventive health services; risk factors; surveys and questionnaires; united nations